2021
DOI: 10.1101/2021.04.23.21255971
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 vaccination beliefs, attitudes, and behaviours among health and social care workers in the UK: a mixed-methods study

Abstract: BackgroundThe UK began delivering its COVID-19 vaccination programme on 8 December 2020, with health and social care workers (H&SCWs) given high priority for vaccination. Despite well- documented occupational exposure risks, however, there is evidence of lower uptake among some H&SCW groups.MethodsWe used a mixed-methods approach - involving an online cross-sectional survey and semi- structured interviews – to gain insight into COVID-19 vaccination beliefs, attitudes, and behaviours amongst H&SCWs … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 18 publications
(7 reference statements)
1
2
0
Order By: Relevance
“…especially when these passports cover domestic activities as opposed to international travel. These findings are in alignment with recent evidence in the UK that suggests thtat health and social care workers who feel pressured to vaccinate are less likely to vaccinate [27]. In overall terms, then, our findings point to a scenario in which passports may accelerate the rate at which maximum numbers of the population are vaccinated while simultaneously lowering the level of that maximum.…”
Section: Discussionsupporting
confidence: 89%
“…especially when these passports cover domestic activities as opposed to international travel. These findings are in alignment with recent evidence in the UK that suggests thtat health and social care workers who feel pressured to vaccinate are less likely to vaccinate [27]. In overall terms, then, our findings point to a scenario in which passports may accelerate the rate at which maximum numbers of the population are vaccinated while simultaneously lowering the level of that maximum.…”
Section: Discussionsupporting
confidence: 89%
“…Overall, this remaining group expresses lower intentions to get vaccinated when vaccine passports are mentioned, especially when these passports cover domestic activities as opposed to international travel. Recent evidence among health and social care workers in the UK suggests that feeling pressured to vaccinate is associated with lower uptake 29 .…”
Section: Discussionmentioning
confidence: 99%
“…1 In Papua New Guinea (PNG), similar to other countries, false information and negative perceptions about COVID-19 in general and vaccination in particular has caused delays in vaccination uptake. 2 Studies have shown that vaccine acceptance among health care professionals is problematic. 3 Although the reluctance identi ed for the COVID-19 vaccine was higher than that seen for vaccines like human papillomavirus (HPV) in 2006 and measles-rubella (MR) in 1963, vaccine hesitancy to a newly released vaccine is not novel and has also been evident with previously introduced vaccines.…”
Section: Introductionmentioning
confidence: 99%